2007
DOI: 10.1093/bja/aem089
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery stents and non-cardiac surgery

Abstract: The utility of interventional cardiology has developed significantly over the last two decades with the introduction of coronary angioplasty and stenting, with the associated antiplatelet medications. Acute coronary stent occlusion carries a high morbidity and mortality, and the adoption of therapeutic strategies for prophylaxis against stent thrombosis has major implications for surgeons and anaesthetists involved in the management of these patients in the perioperative period. Currently, there is limited pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 136 publications
(86 reference statements)
2
97
0
4
Order By: Relevance
“…Therefore the safety of anti-thrombotic drug withdrawal and pro-haemostatic interventions should be considered carefully through a multi-disciplinary risk assessment. If anti-platelet agents are withdrawn they should be re-instated as soon as possible after haemostasis is secured (Howard-Alpe et al, 2007;Bhala et al, 2011;Korte et al, 2011). Platelet transfusion may be considered for emergency reversal of the anti-platelet effect but may confer a risk of arterial thrombosis.…”
Section: Anti-platelet Drugsmentioning
confidence: 99%
“…Therefore the safety of anti-thrombotic drug withdrawal and pro-haemostatic interventions should be considered carefully through a multi-disciplinary risk assessment. If anti-platelet agents are withdrawn they should be re-instated as soon as possible after haemostasis is secured (Howard-Alpe et al, 2007;Bhala et al, 2011;Korte et al, 2011). Platelet transfusion may be considered for emergency reversal of the anti-platelet effect but may confer a risk of arterial thrombosis.…”
Section: Anti-platelet Drugsmentioning
confidence: 99%
“…According to some authors a discontinuation of antiplatelet therapy prior to surgery is suggested to prevent major bleeding [5]. This brings to a high risk of in-stent thrombosis resulting in myocardial infarction with catastrophic outcomes in such patients [5].…”
Section: Discussionmentioning
confidence: 99%
“…La introducción de la angioplastia no tuvo como consecuencia un empeoramiento de los resultados quirúrgicos, incluso cuando la cirugía tenía lugar tan sólo 11 días después de dicha intervención coronaria percutánea (ICP) 129 . Sin embargo, a mediados de la década de los noventa, el desarrollo de la implantación de stents cambió la situación drásticamente y se han observado altas tasas de mortalidad (hasta el 20%) asociadas a la trombosis aguda del stent en el momento de la cirugía, si ésta tenía lugar a las pocas semanas de la implantación y se suprimía el tratamiento antiplaquetario 130,131 . Por este motivo se prefiere posponer la cirugía electiva como mínimo 6 semanas y mejor hasta 3 meses tras la implantación de stents sin recubrir y mantener el tratamiento anreiniciarse 1-2 días después de la intervención, dependiendo del estado hemostático del paciente, y como mínimo 12 h después del procedimiento.…”
Section: Aspirinaunclassified
“…La dosis máxima de sulfato de protamina es de 50 mg. En pacientes tratados con HBPM, el efecto anticoa-tiplaquetario doble. En los casos en que se respetó este periodo de espera, la interrupción del tratamiento antiplaquetario doble se asoció a un aumento de la incidencia de trombosis del stent 130,131 . Transcurridos 3 meses, los pacientes pueden ser sometidos a cirugía no cardiaca manteniéndose, como mínimo, el tratamiento con aspirina ( fig.…”
Section: Aspirinaunclassified